Influence of COVID‐19 on the next generation of nurses in the United States. Issue 3 (18th January 2022) - Kells, Meredith; Jennings Mathis, Karen
Abstract: Aims/Objectives: Examine the affective state (anxiety, depression), life satisfaction, stress and worry, media consumption and perceptions of pursuing a career in nursing amidst the COVID‐19 pandemic. Background: Nursing students worldwide have reported increased stress, fear and anxiety amidst challenges and risks associated with COVID‐19. It remains unclear what impact COVID‐19 will have on nursing students in the United States (US) as they prepare to enter the workforce. Design: Cross‐sectional study of undergraduate nursing students at one university in the Northeastern United States. Methods: Students ( N = 161) completed an online survey (July 2020) about health and life satisfaction, affective state (depression, anxiety), stress and interest in pursuing nursing. Descriptive statistical analysis described sample and quantitative data. Linear regression was used to examine whether media consumption, stress, affective states predicted interest in pursuing a nursing career. Qualitative thematic analysis was applied to the open‐ended question, 'How has COVID‐19 influenced your interest in pursuing a nursing career?'. The Standards for Reporting Qualitative Research (SRQR) checklist was used to evaluate methodological quality. Results: Mean stress score was 56.6 (range 0–100), 55.6% of respondents felt unsettled about the future, and 68.2% reported feeling overwhelmed. 18.7% of students reported moderate to severe anxiety, 19.8% reported moderate to severe depression and 54.4% reported that COVID‐19 influenced their interest in nursing. Six themes emerged from qualitative analysis: no change, reaffirming/confirmatory, importance of nursing, reality check, positive influence and negative influence. Conclusions: Universities/colleges and nursing faculty should prioritise universal mental health assessment for nursing students and enhance mental health services to support and monitor this population. Relevance to clinical practice: Mental health services to support nursing students are warranted in the wake of the COVID‐19 pandemic. Reduction in nursing workforce may have significant impacts on staffing ratios, patient outcomes, nurse burn‐out and other aspects of clinical care.